2007
DOI: 10.1007/s11151-007-9151-y
|View full text |Cite
|
Sign up to set email alerts
|

Economics at the FTC: Pharmaceutical Patent Dispute Settlements and Behavioral Economics

Abstract: Antitrust, Behavioral economics, Consumer protection, FTC, Patents, Pharmaceuticals,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…As in Choi (1998), a finding of patent validity (or invalidity) in the first stage applies equally to 16 In practice, there is a difference between patent infringement and validity, see Shapiro (2003). A challenger may be found not to infringe a patent, but the patent is still valid.…”
Section: The Description Of the Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…As in Choi (1998), a finding of patent validity (or invalidity) in the first stage applies equally to 16 In practice, there is a difference between patent infringement and validity, see Shapiro (2003). A challenger may be found not to infringe a patent, but the patent is still valid.…”
Section: The Description Of the Modelmentioning
confidence: 98%
“…16 We assume that both litigation and settlement are costless. The incumbent wins his case with probability  (patent strength), which is not known before a firm enters the market and sunks  .…”
Section: The Description Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous analysis has shown that under the rule of per se legality settling companies sustain monopoly for the whole patent duration. Thus, initiated challenges do not lead to 22 We analyze the case when companies optimally choose t rr g1 = 1 in Appendix A1.…”
Section: Welfare Analysismentioning
confidence: 99%